Chest Pain Secondary to Use of Oxytocin in Obstetric Patients at Transanesthesic - Iparrea Ramos Ilse Cristina1, Atanacio-González Miriam; Valeria, Jiménez-Báez María; Angel, Medina-Andrade Luis; Horacio, Márquez-Gónzalez; Leobardo, Ureña-Bogarín Enrique; Luis, Sandoval-Juarado (International Journal of Innovative Research in Medical Science, 2017)
Background and objectives - Chest pain is related with the use of oxytocin administration for bleeding control during caesarean or birth. The objective of this study is to evaluate the incidence of chest pain with the use of oxytocin during caesarean operation. Methods - Prospective study of one-cohort including 415 obstetric patients in who was administered oxytocin during caesarean operation. Previous chest pain and use of oxytocin were identified, as anesthesia type and technique used in each case. Clinical and sociodemographic data were identified and reported. Cero point was settled at admission time, the presence of chest pain was considered as outcome event. Clinical data like blood pressure, heart rate, oxygen saturation, electrocardiographic (EKG) anomalies, chest pain, flushing and restlessness were evaluated at 1, 3, 5, 10, 15 and 20 minutes from administration. Long Rank test was used to probe hypothesis, and Kaplan Maier curve for outcome measure. Results - 415 women of 26.5 + 8.5 years were included, 88% receive urgent caesarean operation and in 22% labor was induced. Oxytocin bolus of 5 Units (U) were administered in 110 patients (26.5%). Infusion doses was from 10 to 25 U. Chest pain was present in 83(20%) (p=0.005), tachycardia in 152(36.62%)(p=0.001), hypotension in 81(19.5%)(p=0.702), flushing in 55(13.25%)(p=0.185), discomfort in 212(51.08%)(p=0.019), EKG changes in 4(0.96%)(p=0.001) and others in 4 cases (0.96%). Log Rank = 0.014. Conclusions - Oxytocin administration is not harmless and must be used carefully, because high and constant doses increase the secondary cardiovascular effects significantly.